Changes in the availability of clinical practice guidelines for malnutrition: A 6-y multicenter study - Blanař, Mgr Vít; Eglseer, Doris; Lohrmann, Christa; Hödl, Manuela (Nutrition (Burbank, Los Angeles County, Calif.), 2020)
OBJECTIVE: The aim of the study was to examine the availability of clinical practice guidelines for malnutrition in hospitals over a period of 6 y and the subsequent use of nutritional interventions in malnourished patients. METHODS: This study was conducted as a secondary data analysis of data that were collected from 2012 to 2017 in a quantitative, cross-sectional, multicenter study called the National Prevalence Measurement Quality of Care (LPZ). Data from 15 hospitals and 5650 participating patients were analyzed. RESULTS: The availability of clinical practice guidelines for malnutrition at the institutions increased from 6.7% in 2012 to 100% in 2017 (P < 0.001). The control of compliance to the guidelines increased from 28.6% to 85.7% (P < 0.001) and the documentation of malnutrition risk improved from 63.1% to 87.5% (P = 0.008). In 2017, the intervention "referral to dietitian" was used 8.3% more often (P < 0.001). The number of patients who did not receive any intervention decreased from 70% in 2012 to 55.6% in 2017 (P < 0.001). CONCLUSIONS: The availability of guidelines on malnutrition increased in participating hospitals over the 6-y study period. Regular controls of adherence to the guidelines positively correlated with their availability. More interventions to treat malnutrition were carried out in 2017. The use of clinical practice guidelines in this study was associated with more interventions treating malnutrition.
Keywords: Interventions; kvalita zdravotní péče; Health Care Surveys; Humans; Availability; Guideline Adherence; prevalence; lidé; Nutrition Therapy; Clinical practice guidelines; Nutrition Assessment; Malnutrition; podvýživa; hodnocení stavu výživy; Practice Guidelines as Topic; dodržování směrnic; Hospitals; Quality of Health Care; nemocnice; nutriční terapie; směrnice pro lékařskou praxi jako téma; Risk assessment; Cross-Sectional Studies; průzkumy zdravotní péče; průřezové studie; Prevalence; Risk Assessment; hodnocení rizik; Compliance